Leverage Points as an Analytical Framework for Preventing Rebound Effects: An Exploratory Study - Mckay, Lukas; Meneguim , Lucas; Guzzo, Daniel; Pigosso, Daniela C. A. (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Despite global efforts toward sustainability, greenhouse gas emissions continue to rise, partly due to rebound effects (RE), i.e., systemic responses that offset the potential sustainability benefits of sustainability interventions. Designers often struggle to prevent RE due to dynamic complexities characterized by non-linearity, feedback loops, and delays. This paper explores how systems thinking, specifically the Leverage Points Framework (LPF), can support design activities in ideating and designing strategies for preventing RE. Through an exploratory case study of an electric car-sharing system, LPF and ideation techniques were applied to devise potential design strategies to prevent RE emerging from five identified RE mechanisms. Our findings suggest that integrating leverage points into the design process encourages a more systemic and comprehensive approach to ideation, expanding design opportunities towards the prevention of RE. We conclude that combining systems thinking with design thinking enhances the potential for creating effective, sustainable interventions and recommend further research to evaluate the practical potential of the proposed framework.